2008
DOI: 10.1097/sap.0b013e3181561500
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Doppler Sonography and Multidetector-Row Computed Tomography in the Imaging findings of the Deep Inferior Epigastric Perforator Artery

Abstract: MDCT angiography is useful for preoperative planning of deep inferior epigastric artery perforator flap at the point of more accurate anatomical findings and clear images of perforator vessels compared to the findings using Doppler ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
0
22
1
3
Order By: Relevance
“…Many modalities are available for preoperative perforator mapping, such as Doppler ultrasonography, color Doppler ultrasonography, CT angiography, and magnetic resonance angiography, and each has its advantages and disadvantages [34][35][36][37][38][39][40][41]. Handheld Doppler ultrasonography is convenient, quick, and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…Many modalities are available for preoperative perforator mapping, such as Doppler ultrasonography, color Doppler ultrasonography, CT angiography, and magnetic resonance angiography, and each has its advantages and disadvantages [34][35][36][37][38][39][40][41]. Handheld Doppler ultrasonography is convenient, quick, and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…From our comparative study, it can be concluded that color Doppler ultrasound is more accurate than computed tomographic angiography in the preoperative mapping of perforators in the lower extremity. This is quite different from the established position that computed tomographic angiography performs better than color Doppler ultrasound 14,15 when applied to perforators of the abdomen. This may be explained by two anatomical characteristics of the lower extremity: the relatively thin subcutaneous tissue and its tube-like three-dimensional structure.…”
Section: Cta (%) Cdu (%) Cta (%) Cdu (%)mentioning
confidence: 95%
“…Of all the available methods, computed tomographic angiography and color Doppler ultrasound are the mostly widely applied in the clinical setting. 12,13 Computed tomographic angiography performs better than color Doppler ultrasound 14,15 when applied to perforators of the abdomen, and has been considered as the gold standard in preoperative deep inferior epigastric perforator flap evaluation. 16,17 The anatomy of the lower limb, however, differs greatly from that of the abdomen.…”
mentioning
confidence: 99%
“…Biocompatible hydrocolloid dressings (HDs) were developed as a new type of material for skin injury and showed therapeutic efficacy, but were unsatisfactory for treating deep partial‐thickness or full‐thickness wounds. Moreover, HDs turned out to have some complications, especially stripping of the regenerated epidermis at the time of the detachment procedure because of their adherence property …”
mentioning
confidence: 99%
“…Moreover, HDs turned out to have some complications, especially stripping of the regenerated epidermis at the time of the detachment procedure because of their adherence property. 3,4 In cases with deep partial-thickness and full-thickness wounds, optimization of extracellular matrix (ECM) components, especially collagen, is needed for proper tissue repair. Collagen sponges (CSs) are frequently placed on a wound with or without cell components.…”
mentioning
confidence: 99%